Resiliensi Digital Siswa Smp Terhadap Hoax Dan Cyberbullying: Kajian TentangKesadaran Hukum Dan Literasi Digital - Nadya Mahamida; Qitallya Adinda Zahrani; Wilda Efendi Ruslan; Marsela Marsela; Lisa Lorensa; Anisa Dwi Lestari; Dhea Novitasi; Dina Ramadhani; Izwah Marhamah; Dea Azahra; Febra Anjar Kusuma (Jurnal Ilmu Pendidikan Pancasila, Kewarganegaraan, dan Hukum, 2026)
The development of digital technology has increased adolescents' access to the internet while also exposing them to various digital risks, such as misinformation, cyberbullying, and privacy violations. This condition highlights the importance of digital resilience as the ability to cope with and manage challenges in the digital environment. Digital literacy and legal awareness are essential factors in strengthening digital resilience, enabling adolescents to use technology critically, safely, and responsibly. Therefore, strengthening these aspects is necessary to develop a resilient young generation in the digital era.